Representasi Folksong dan Memori Kinetik dalam Nyanyian Jemaat Gereja Protestan Maluku - Mahoklory, Novian Hendrik; Lattu, Izak Y.M; Lauterboom, Mariska (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2024)
This article aims to examine the Maluku Protestant Church (GPM) Congregation Songbook using the kinetic memory study to find the representation of folksong in implementing worship in Maluku.  The author uses descriptive qualitative methods with data collection techniques and interviews with key informants, including the GPM synod chairman and two songwriters from this congregational songbook, to obtain the desired results. Based on the results of the research, the author found that it is true that the GPM congregational songbook is the work of the Maluku people used in the worship life of the Maluku people, which is inseparable from the context of the social and cultural life of the Maluku people so that this congregational song can be referred to as the folksong of the Maluku people which is contextualized by theological and cultural understanding. The next finding also presents several song titles and lyrics that contain kinetic memory so that when sung with body movements, it will liven up the atmosphere of worship that is more vibrant and excite the congregation.